2004
DOI: 10.1002/bdd.425
|View full text |Cite
|
Sign up to set email alerts
|

The utility of mixed‐effects covariate analysis in rapid selection of doses in pediatric subjects: A case study with fexofenadine hydrochloride

Abstract: Fexofenadine hydrochloride is a non-sedating antihistamine that is used in the treatment of symptoms associated with seasonal allergic rhinitis and chronic idiopathic urticaria. A pooled analysis of pharmacokinetic data from children 6 months to 12 years of age and adults was conducted to identify the dose(s) in children that produce exposures comparable to those in adults for the treatment of seasonal allergic rhinitis. The pharmacokinetic parameter database included peak and overall exposure data from 269 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…The bioavailability of fexofenadine in man has not been determined in detail, but appears to be higher than in horse and mouse (Lippert et al. , 1995; Krishna et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of fexofenadine in man has not been determined in detail, but appears to be higher than in horse and mouse (Lippert et al. , 1995; Krishna et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…administration of fexofenadine in horse the C max in plasma was about 86 ng/mL after dosing at 10 mg/kg bw. This can be compared with man, in which the C max in serum was reported to be about 450 ng/mL after oral doses of about 3 mg/kg bw of fexofenadine (Krishna et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Fexofenadine was well tolerated, and no unexpected AEs were observed. Population analysis showed that the apparent oral clearance estimate of fexofenadine was 36% lower in pediatric subjects 2 to 5 years compared to adult subjects . As the clinical formulation in the PK and safety studies were not suited for marketing, an oral suspension formulation was developed later as the to‐be‐marketed formulation.…”
Section: Antihistaminesmentioning
confidence: 99%
“…Population analysis showed that the apparent oral clearance estimate of fexofenadine was 36% lower in pediatric subjects 2 to 5 years compared to adult subjects. 21,71 As the clinical formulation in the PK and safety studies were not suited for marketing, an oral suspension formulation was developed later as the to-be-marketed formulation. The formulation bridging program comprised of three PK studies to evaluate the bioavailability, bioequivalence and food effect of the suspension formulation.…”
Section: Fexofenadinementioning
confidence: 99%
“…Krishna et al. [12] showed also the utility of this approach in rapid selection of doses of fexofenadine in paediatric patients. As clinical development of drugs in adults usually precedes that in children, the PK data accumulated in adults should help the analysis of those from children.…”
Section: Combining Children and Adults Datamentioning
confidence: 99%